Maggot excretion products from the blowfly Lucilia sericata contain contact phase/intrinsic pathway-like proteases with procoagulant functions - Kahl, Mareike; Gökçen, Anke; Fischer, Silvia; Bäumer, Markus; Wiesner, Jochen; Lochnit, Günter; Wygrecka, Malgorzata; Vilcinskas, Andreas; Preissner, Klaus T. (Thrombosis and Haemostasis, 2015)
For centuries, maggots have been used for the treatment of wounds by a variety of ancient cultures, as part of their traditional medicine. With increasing appearance of antimicrobial resistance and in association with diabetic ulcers, maggot therapy was revisited in the 1980s. Three mechanisms by which sterile maggots of the green bottle fly Lucilia sericata may improve healing of chronic wounds have been proposed: Biosurgical debridement, disinfecting properties, and stimulation of the wound healing process. However, the influence of maggot excretion products (MEP) on blood coagulation as part of the wound healing process has not been studied in detail. Here, we demonstrate that specific MEP-derived serine proteases from Lucilia sericata induce clotting of human plasma and whole blood, particularly by activating contact phase proteins factor XII and kininogen as well as factor IX, thereby providing kallikrein-bypassing and factor XIa-like activities, both in plasma and in isolated systems. In plasma samples deficient in contact phase proteins, MEP restored full clotting activity, whereas in plasma deficient in either factor VII, IX, X or II no effect was seen. The observed procoagulant/intrinsic pathway-like activity was mediated by (chymo-) trypsin-like proteases in total MEP, which were significantly blocked by C1-esterase inhibitor or other contact phase-specific protease inhibitors. No significant influence of MEP on platelet activation or fibrinolysis was noted. Together, MEP provides contact phase bypassing procoagulant activity and thereby induces blood clotting in the context of wound healing. Further characterisation of the active serine protease(s) may offer new perspectives for biosurgical treatment of chronic wounds.
Keywords: Maggot therapy; Lucilia sericata; wound repair; blood coagulation; contact phase proteins